Snooze - Rafael, Nur Amira Rifqah; Amiralam, Farah Raihana; Ismail, Noorfazilla; Kastian, Nur Hazwani; Royasee, Raniafatira; Salem, Siti Noor Haseenah; Sabransah, Sitti Shahmiezan (2016)
Snooze is a private napping station for public spaces provides private, secure, and clean accommodations anywhere, a brand offering a bed and associated facilities in a limited space which is known as sleep box. It is a larger version of a capsule hotel. At Snooze, we imagine a world where creative, collaborative, and self-driven individuals discover their full potential by integrating work, life, and creative experiences. We know that by removing boundaries we all explore our potential to actualize our health, happiness, and creativity. By integrating a wealth of experiences, we empower personal development by growing toward the best versions of ourselves. We want to provide a comfortable space and conducive rest stop for the customers especially those who travel by road. We have developed Snooze to facilitate everyone working and living at their peak levels. We achieve success by increasing the degree and quality of worklife integration, and by providing the flexibility to find the dynamic balance in our daily lives. Snooze facilitates easy and expansive travel by providing any traveler access to the most remote or desired locations. Convenience and ease of use allow you to recharge in your Snooze, then step right back into the center of attention. We empower local entrepreneurs to expand their business or actualize their vision by offering low entry costs for establishing new Snooze franchises. Our flexible licensing plans also allow for existing business operators to grow their capabilities.